Justice League starcrossed - Lukic, Butch; Riba, Dan.; Fogel, Rich.; Ridely, John.; McDuffie, Dwayne; Timm, Bruce; Tucker, James; Warner Home Video; Warner Home Video (Phils.). (Burbank, Calif. Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2004)
When a Thanagarian spaceship descends upon Earth, the Justice League turns to Hawkgirl for some answers. And their questions multiply when they discover she has been living amongst them as a spy! As the Thanagarian visitors reveal their dark intentions, Hawkgirl must choose between loyalty to her people and love for her friends on her adopted planet Earth.
Based on DC Comics characters.
Animation directors, Young Ho Kim, Baek Soo Kim, Sung Man Huh ; editor, Joe Gall ; music, Lolita Ritmanis, Michael McCuistion, Kristopher Carter ; character designers, Robert Fletcher ... [et al.]
Voices: Maria Canals, Phil Lamarr, Kevin Conroy, George Newbern, Susan Eisenberg, Carl Lumbly, Michael Rosenbaum, Victor Rivers, Hector Elizondo, Elizabeth Peña.
MPAA rating: Not rated.
VCD
Keywords: Justice League of America (Fictitious characters) -- Juvenile drama